2014
DOI: 10.1002/jhm.2225
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hospital Consumer Assessment of Healthcare Providers and Systems patient satisfaction scores for specialty hospitals and general medical hospitals: Confounding effect of survey response rate

Abstract: BACKGROUND Specialty hospitals are a subset of acute‐care hospitals that provide a narrower set of services than general medical hospitals (GMHs), predominantly in areas such as cardiac disease and surgery. Although specialty hospitals also advertise high patient satisfaction, this has not been examined using national data. We examined the differences in Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) satisfaction scores in a national sample. METHODS HCAHPS results were obtained for J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 10 publications
1
44
1
Order By: Relevance
“…Although analysis of HCAHPS scores is also subject to nonresponse bias, HCAHPS surveys are conducted independently and likely reflect a similar response bias that would be expected to be seen at other institutions and reflect the real-life responses used for hospital comparison and value-based payment. We were unable to assess true response rates in this study owing to CMS sampling methods; however, the proportion of patients with a returned survey in the present study was only slightly lower than a recently reported mean survey response rate for HCAHPS surveys across all hospitals in the United States 27 . Last, comparisons between patients admitted to a neurology service and those on general medical and neurosurgical-specific services should be interpreted with caution because the present multivariable analysis is likely unable to adjust for the inherent differences in patient populations.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Although analysis of HCAHPS scores is also subject to nonresponse bias, HCAHPS surveys are conducted independently and likely reflect a similar response bias that would be expected to be seen at other institutions and reflect the real-life responses used for hospital comparison and value-based payment. We were unable to assess true response rates in this study owing to CMS sampling methods; however, the proportion of patients with a returned survey in the present study was only slightly lower than a recently reported mean survey response rate for HCAHPS surveys across all hospitals in the United States 27 . Last, comparisons between patients admitted to a neurology service and those on general medical and neurosurgical-specific services should be interpreted with caution because the present multivariable analysis is likely unable to adjust for the inherent differences in patient populations.…”
Section: Discussioncontrasting
confidence: 75%
“…In addition, published CMS patient-mix adjustment of HCAHPS scores shows that surgical patients provide higher ratings on all composite measures except for Communication With Nurses. Not only has variation been shown across hospitals of different types, 27 but this study's finding of variation between services within a single institution is also consistent with a previous publication that found that HCAHPS scores varied widely across surgical specialties 12 . This suggests that HCAHPS scores reflect patient factors that vary across both surgical and medical specialties and are not accounted for in current HCAHPS case-mix adjustment, which is limited to age, educational level, admission type (medical vs surgical vs maternity), patient-reported overall health rating, language, and response percentile 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Small hospitals (<100 beds), nonurban hospitals, those with Magnet status for nursing, and those with higher nurse-to-patient-days ratios also tend to perform better on Adult HCAHPS measures. 32, 3436 The contrasting findings regarding volume for Child versus Adult HCAHPS might be explained by the lower numbers of eligible discharges from pediatric wards within large general hospitals than from freestanding children’s hospitals or children’s hospitals within a hospital.…”
Section: Discussionmentioning
confidence: 99%
“…; Siddiqui et al. ). Furthermore, nurse staffing and patient experience are likely to be correlated with many characteristics of a hospital's patient case mix, including age, sex, race, health status, and education (Elliott et al.…”
Section: Conceptual Frameworkmentioning
confidence: 99%